Advances and prospects in SAR microwave vision <?A3B2 pi6?>three-dimensional imaging - Qiu Xiaolan; Jiao Zekun; Zhang Zhe; Yan Qiancheng; Ding Chibiao (National Science Open)
Synthetic Aperture Radar three-dimensional (3D) imaging enables the acquisition of more comprehensive information, making it a recent hotspot in radar imaging. Traditional 3D imaging methods have evolved from 2D and interferometric imaging, combining elevation aperture extension with signal processing techniques. Limitations such as long acquisition or complex system from its imaging mechanism restrict its application. In recent years, rapid development of artificial intelligence has led to a swift advancement in radar, injecting new vitality into SAR 3D imaging. SAR microwave vision 3D imaging theory, which is built upon advanced technologies, has emerged as a new interdisciplinary field for radar imaging. This paper reviews SAR 3D imaging’s history and present situation, and introduces SAR microwave vision. We establish a theoretical framework covering representation models, computational models, processing paradigms and evaluation systems. Additionally, our research progress in this area is discussed, along with future prospects for SAR microwave vision 3D imaging.